Novel Human Tenascin-C Function-Blocking Camel Single Domain Nanobodies - Dhaouadi, Sayda; Ben Abderrazek, Rahma; Loustau, Thomas; Abou-Faycal, Chérine; Ksouri, Ayoub; Erne, William; Murdamoothoo, Devadarssen; Mörgelin, Matthias; Kungl, Andreas; Jung, Alain; Ledrappier, Sonia; Benlasfar, Zakaria; et al. (Frontiers in Immunology, 2021)
The extracellular matrix (ECM) molecule Tenascin-C (TNC) is well known to promote tumor progression by multiple mechanisms. However reliable TNC detection in tissues of tumor banks remains limited. Therefore, we generated dromedary single-domain nanobodies Nb3 and Nb4 highly specific for human TNC (hTNC) and characterized the interaction with TNC by several approaches including ELISA, western blot, isothermal fluorescence titration, negative electron microscopic imaging. Our results revealed binding of both nanobodies to distinct sequences within fibronectin type III repeats of hTNC. By immunofluroescence and immune histochemical imaging we observed that both nanobodies detected TNC expression in PFA and paraffin embedded human tissue from ulcerative colitis, solid tumors and hepatic metastasis. As TNC impairs cell adhesion to fibronectin we determined whether the nanobodies abolished this TNC function. Indeed, Nb3 and Nb4 restored adhesion of tumor and mesangial cells on a fibronectin/TNC substratum. We recently showed that TNC regulates the immune-suppressive tumor microenvironment by chemoretention immobilizing dendritic cells in the stroma. Here, we document that immobilization of DC2.4 dendritic cells by a CCL21 adsorbed TNC substratum was blocked by both nanobodies. Altogether, our novel TNC specific nanobodies could offer valuable tools for detection of TNC in the clinical practice and may be useful to inhibit the immune-suppressive functions of TNC in cancer.